The Impact of Service Quality and Profit-Sharing System on Customer Satisfaction Using Easy Mudharabah Savings Products (Study on Customers of Bank Syariah Indonesia Banjarbaru Branch Office) - Muyasarah, Iin; Amelia, Zaida; Malihah, Lola (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
Islamic banks play an important role as facilitators in all economic activities including in the field of fund management. One of the products is Easy Mudharabah Savings. This research is field research with a quantitative approach that aims to determine the impact of service quality and the profit-sharing system on customer satisfaction. This research hypothesizes that service quality and the profit-sharing system are thought to influence the satisfaction of Easy Mudharabah savings customers. The population is 4,035 people, the sample is 100 people with the Probability Sampling technique. Data analysis in this study uses descriptive analysis and multiple linear regression. Based on Multiple Linear Regression calculations, the results of the F-test (Simultaneous), F-Count 17.522, and F-Table 2.36 were obtained with a significance level of 0.000 <0.10, meaning that simultaneous service quality (X1) and profit-sharing (X2) have a significant impact on customer satisfaction. Based on the results of the T-test analysis (Partial), the service quality variable (X1) T-count is 2.571 and T-table 1.661 with a significance level of 0.014 <0.10, meaning that there is a significant influence of service quality on customer satisfaction. Meanwhile, the profit-sharing variable (X2) T-count is 4.674 and T-table is 1.661 with a significance of 0.000 <0.10, meaning that there is a significant influence of service quality on customer satisfaction. The variables service quality (X1) and profit-sharing (X2) influence customer satisfaction (Y) by 67.9% while the remaining 32.1% is influenced by other variables outside this research.